Family dynamics and depression in cancer patients with chemotherapy at the Regional Institute of Neoclassical Diseases (IREN) Arequipa 2014 - Alejandra Lazo del Carpio (2018)
This study aims to establish the association between functional and dysfunctional family and the level of depression in patients with cancer chemotherapy IREN. The relationship between two factors was established by applying two tests depression scale Zung and questionnaire Family Apgar, by way of personal interviews with 140 patients of different sex, age 20, diagnosed with cancer admitted to the IREN receiving chemotherapy during the months of August to November 2014. The results show that 89.3% of patients have depression ranging from mild to severe in 67.8% of families of patients no family dysfunction, using the chi square test P<(0.01) it was established that no relationship between family functioning and depression levels. No relationship was found in the presence of depression, family functioning between men and women, nor between the time of illness depression and family functioning. Finally, no correlation was found between the time of illness, depression and family dysfunction. Finally, no correlation was found between the Patient Sex, time of illness, depression and family dysfunction